Pretreatment Diffusion-Weighted MRI Can Predict the Response to Neoadjuvant Chemotherapy in Patients with Nasopharyngeal Carcinoma. (27th August 2015) - Zhang, Guo-Yi; Wang, Yue-Jian; Liu, Jian-Ping; Zhou, Xin-Han; Xu, Zhi-Feng; Chen, Xiang-Ping; Xu, Tao; Wei, Wei-Hong; Zhang, Yang; Huang, Ying
Abstract : Purpose . To explore the potential of diffusion-weighted (DW) magnetic resonance imaging (MRI) using apparent diffusion coefficient (ADC) for predicting the response to neoadjuvant chemotherapy in nasopharyngeal carcinoma (NPC). Methods and Materials . Ninety-two consecutive patients with NPC who underwent three cycles of neoadjuvant chemotherapy were retrospectively analyzed. DW and anatomical MRI were performed before and after neoadjuvant chemotherapy prior to radiotherapy. Pretreatment ADCs and percentage increases in ADC after chemotherapy were calculated for the primary lesions and metastatic adenopathies. Receiver operating characteristic curve analysis was used to select optimal pretreatment ADCs. Results . Pretreatment mean ADCs were significantly lower for responders than for nonresponders (primary lesions, P = 0.012 ; metastatic adenopathies, P = 0.013 ). Mean percentage increases in ADC were higher for responders than for nonresponders (primary lesions, P = 0.008 ; metastatic adenopathies, P < 0.001 ). The optimal pretreatment primary lesion and metastatic adenopathy ADCs for differentiating responders from nonresponders were 0.897 × 10 −3 mm 2 /sec and 1.031 × 10 −3 mm 2 /sec, respectively. Conclusions . NPC patients with low pretreatment ADCs tend to respond better to neoadjuvant chemotherapy. Pretreatment ADCs could be used as a new pretreatment imaging biomarker of response to neoadjuvant chemotherapy.